Analysis and Design of Complementary Ring Type Metamaterial Filter in THz Wave Domain - Wu Pan; Jun Chen; Tianbo Duo; Zichen Liu (Indonesian Journal of Electrical Engineering and Computer Science, 2014)
In this paper, the complementary ring type metamaterial unit is theoretically analyzed by using the spectral domain approach. A terahertz bandpass filter is designed, which consists of triple-layer complementary ring metamaterial. The center frequency of the filter is 338GHz, the transmission rate in pass band reaches 97%, the maximum insertion loss in pass band reaches 0.62dB and 3dB bandwidth reaches 75.9GHz. The filter shows stable filtering properties at different polarization wave and the same polarized wave at different incident angles within the scope of 20°. The range of operating frequency matches the first terahertz atmosphere communication window, so it can be used in the field of terahertz atmosphere communication.